Predictive Analysis Pendidikan Menggunakan Machine Learning di Sumatera Barat - Fitri Rahmah Ul Hasanah; Muhammad Kivlan Reftreka Nugraha (JOSTECH Journal of Science and Technology, 2023)
This study uses big data, namely the socio-economic 2019 data. The focus of this research is Education. Education is an important factor in life, but in West Sumatra using the socio-economic 2019 data it is still in the low category and far from the national average. In this study will predict the factors that influence education in West Sumatra with the data classification method. Methods for classifying large amounts of data have been developed, including Machine Learning. Machine Learning is a field of technology that is currently being widely used to create algorithms with large data (big data). The machine learning method used is Naive Bayes and Bagging. Furthermore, the two models were tested and showed that the Naive Bayes model gave the best performance compared to the Bagging model based on the values of accuracy, sensitivity and specificity. So the Naive Bayes model is the best machine learning model for predicting the factors that affect education, namely household members, gender and regional classification.